Directional compass preference for landing in water birds - Hart, Vlastimil; Malkemper, Erich Pascal; Kušta, Tomáš; Begall, Sabine; Nováková, Petra; Hanzal, Vladimír; Pleskač, Lukáš; Ježek, Miloš; Policht, Richard; Husinec, Václav; Cervený, Jaroslav; Burda, Hynek (Frontiers in zoology, 2013)
INTRODUCTION: Landing flight in birds is demanding on visual control of velocity, distance to target, and slope of descent. Birds flying in flocks must also keep a common course of landing in order to avoid collisions. Whereas the wind direction may provide a cue for landing, the nature of the landing direction indicator under windless conditions has been unknown. We recorded and analysed landing directions of 3,338 flocks in 14 species of water birds in eight countries. RESULTS: We show that the preferred landing direction, independently of the direction from which the birds have arrived, is along the north-south axis. We analysed the effect of the time of the year, time of the day (and thus sun position), weather (sunny versus overcast), light breeze, locality, latitude, and magnetic declination in 2,431 flocks of mallards (Anas platyrhynchos) and found no systematic effect of these factors upon the preferred direction of landing. We found that magnetic North was a better predictor for landing direction than geographic North. CONCLUSIONS: In absence of any other common denominator determining the landing direction, the alignment with the magnetic field lines seems to be the most plausible if not the only explanation for the directional landing preference under windless and overcast conditions and we suggest that the magnetic field thus provides a landing direction indicator.